Analysis of MSC and EVS-MSC administration to the liver of biliary atresia model rats using liquid chromatography-mass spectrometry examination - Naldi, Yandri; Jusuf, Ahmad Aulia; Antarianto, Radiana D; Brajadenta, Gara S; Simorangkir, Rico D (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the therapeutic potential of mesenchymal stem cells (MSCs) and extracellular vesicles derived from MSCs (EVs-MSCs) in reducing toxic compound accumulation in a biliary atresia model. Biliary atresia is a progressive fibro-inflammatory disease of the bile ducts that often requires surgical intervention and liver transplantation, highlighting the need for alternative therapies. Experimental rat livers subjected to bile duct ligation (BDL) were divided into untreated and treated groups. The treated group received MSCs and EVs-MSCs. Liquid chromatography–mass spectrometry (LC-MS) was employed to identify and compare compounds present in both groups. LC-MS analysis revealed 27 compounds in untreated BDL livers, including toxic metabolites such as dimethyl sulfoxide and pyrogallol. In contrast, treated livers exhibited only 18 compounds, notably safer agents such as nicotinamide, butylparaben, caffeine, and indole-3-carbinol. Two compounds, nicotinamide (a vitamin) and butylparaben (an antifungal), were consistently detected in both groups. Importantly, compounds in treated samples were less toxic and potentially protective. Administration of MSCs and EVs-MSCs reduced the presence of harmful compounds, suggesting a protective biochemical effect against biliary atresia progression. These findings provide preclinical evidence that MSC-based therapies may serve as safer, non-toxic alternatives or adjuncts to surgery and transplantation in biliary atresia management.